Genetic Characterization and Population Structure by iPBS Markers of Bottle Gourd (Lagenaria siceraria) Genotypes - Ömer Faruk COSKUN (Journal of Animal and Plant Sciences, 2024)
Bottle gourd (Lagenaria siceraria (Molina) Standl.) is used as a rootstock in vegetable grafting in many parts of the world, benefiting from its strong root structures. In addition, the ripe fruits of this plant species are used as ornaments and the immature fruits are used as vegetables. This study aimed to determine the genetic diversity of bottle gourd genotypes whose fresh fruits are consumed. Using iPBS marker techniques, a total of 186 bands in 30 genotypes were obtained and the polymorphism rate was calculated as 93.3%. Similarity coefficient values were found in the range of 0.35-0.96. Three main clusters emerged in cluster analysis and as a result of the structure analysis, it was determined that the genotypes consisted of four subpopulations. It was concluded that bottle gourd genotypes could be genetically distinguished using the iPBS technique and that the genetic diversity among bottle gourd genotypes was high. These data can be used in breeding strategies to improve bottle gourd varieties.
Keywords: Bottle Gourd; Laneraria siceraria; vegetable; molecular characterization; iPBS